(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the theoretical foundations of developing students’ language competence in the context of educational digitalization. It analyzes the evolution of the concept of language competence in linguistics and pedagogy and describes its structural components within the communicicative approach. Particular attention is paid to the impact of digital technologies on the development of students’ language skills, as well as their role in enhancing learning motivation, learner autonomy, and the effectiveness of language instruction. Based on an analysis of national and international research, the article summarizes contemporary approaches to the use of digital educational resources in the development of language competence.